Considerations about vehicle electrification in Brazil: Facts and concerns - Neto, João Pinto Cabral; Melo, André Luís Canuto Duarte; Cabral, Viviany Christine Rodrigues da Silva; Silva, Elivania de Araújo; Duarte, Arlene Leão de Lima; Cabral, Marlucia Barros Lopes (GOT: Revista de Geografia e Ordenamento do Território, 2026)
Research Purpose: To present a discussion on the main challenges, perspectives, and concerns associated with the implementation of a new transportation paradigm in Brazil: electric vehicles (EVs). Additionally, to conduct a comparative analysis between EVs and internal combustion engine vehicles powered by biofuels. Methodology: Bibliographic research, official databases (number of registered EVs), tax incentives, and government planning policies related to vehicle electrification were employed to assess the impacts and challenges of this emerging urban mobility solution. Furthermore, based on the estimated electricity consumption of a utility-type EV, under Brazilian usage patterns and from the perspective of carbon footprint, a comparative evaluation was conducted between electric vehicle technologies and biofuel-powered vehicles, considering a projected fleet by 2030. Findings: The findings reveal that there are additional concerns beyond those already observed in countries where EVs are widely adopted. These include infrastructural limitations, both in terms of accommodating the increasing electricity demand and ensuring a genuine reduction in atmospheric emissions. The study suggests that although electrification offers clear advantages, technological diversification—such as hybrid vehicles powered by both electricity and biofuels—may represent a promising solution. Consequently, the state of vehicle electrification in Brazil is highlighted, considering its status as a developing country with significant agricultural potential. Originality/Value: EVs, due to their zero tailpipe emissions, have been strongly promoted by governments worldwide, including Brazil. However, Brazil has a long-standing tradition in agricultural production and operates a considerable fleet of vehicles powered by biofuels, which also constitute a sustainable alternative, particularly given the carbon offset through biomass regrowth. This study explores the key challenges of vehicle electrification in Brazil, in light of the specific context of a developing country where agribusiness accounts for over 20% of the Gross Domestic Product.